Mapping the Nexus of Strategic Management and Sustainable Development Goals 12 with a Focus on Innovation: A Bibliometric Analysis - Erika Erika; Bob Subhan Riza; Sabda Maulana; Shakeel Rahagi (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
This study aims to map the research landscape at the intersection of Strategic Management and Sustainable Development Goal (SDGs) 12: Responsible Consumption and Production, using bibliometric methods. A total of 94 articles published between 2015 and 2025 were analyzed using VOSviewer and Bibliometrix to identify key authors, countries, institutions, and thematic clusters. The results revealed four dominant keyword clusters: growth, strategy, innovation, and stakeholder integration. Notably, India emerged as a central player in global collaborations related to SDGs 12. Theoretically, this study extends the understanding of how technological and green innovations intersect within strategic management frameworks to foster sustainable consumption and production practices. Managerially, the findings suggest that organizations should invest in digital infrastructure, particularly in AI, IoT, and data analytics, and adopt cross-sector governance mechanisms to drive sustainability goals. Furthermore, embedding sustainability metrics into key performance indicators (KPIs) can create a competitive advantage while aligning with global sustainability agendas. This paper provides actionable insights for both researchers and managers seeking to integrate strategic innovation with SDGs 12.